TERAPAN RISK ASSESSMENT PADA BAHAYA ENCLOSED SPACE MENGGUNAKAN METODE HAZARD AND OPERABILITY STUDY DI KAPAL MT. CAHAYA MULYA 88 - Akbar Maulana, Hafizh; Imam Firdaus, Muhamad; Nofandi, Faris; Haryanto, Tri (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Enclosed spaces on ships pose significant safety risks due to limited ventilation and hazardous gas accumulation, contributing to frequent maritime accidents globally and in Indonesia. This study aims to apply Hazard and Operability Study (HAZOP) for risk assessment of enclosed space entry operations on MT. Cahaya Mulya 88. Using a qualitative descriptive approach, the population comprised 20 crew members involved in enclosed space operations, with purposive sampling of 5 key informants (safety officer, chief officer, boatswain). Instruments included structured observation sheets, semi-structured interview guides, and HAZOP checklists, analyzed via Miles and Huberman's model (data reduction, display, verification). Results showed initial extreme risks (R=25) in cargo tanks due to hydrocarbon vapors, reduced to low levels (R=2-4) through forced ventilation, LEL sensors, and strict Permit to Work procedures. HAZOP effectively identified operational deviations across manhole, cargo tank, and fresh water tank. The study concludes that systematic HAZOP implementation significantly enhances maritime safety compliance with IMO Resolution A.1050(27) and ISM Code.